Levantamento da diversidade de borboletas em floresta ombrófila aberta em regeneração. - Lima, Alysson dos Santos (2020)
Insects are classified as the only arthropods that fly and one of the most diverse orders of the Insecta class is the Lepidoptera order, composed of butterflies and moths, insects wich respond very easily to environment changes. The open rainforest is a plant formation characterized by a humid forest, with four floristic factions, typical of “brejos de altitude”. This present study aims to accomplish an inventory of butterfly species in an area of Open Rainforest regeneration in the city of Areia - PB. Butterfly collections were realized every two weeks, using active and passive methods between the months of april to november 2018. In all, 200 specimens of 30 species were collected, identified and submitted to analysis of frequency, constancy, wealth and abundance, wherein 150 from the Nymphalidae family, 48 from Pieridae and two from Riodinidae, and the Nymphalidae family amounted 74.5% of the total. The species that stood out were Eurema lirina with 16% of frequency and, followed by, Mechanitis lysimnia nesaea and Taygetis thamyra both with 13%. It was observed that the studied area, even having influences of the notorious anthropization, keeps average standards with regard to the butterflies occurrence in humid forests already very disturbed by human action, occasional reservations. This proposition may be due to the fact that Nymphalidae species adapt with some ease to environmental disturbances, as in the example of butterflies from Satyrinae, the third most collected subfamily.